The Role of Women in Urban Architectural Institutions in Baghdad during the Early Abbasid Period (132–232 AH / 750–847 CE) (The International Journal for Scientific Research, 2026)
This study seeks to examine the role of women in urban architectural institutions in Baghdad during the Early Abbasid period (132–232 AH / 750–847 CE). The research problem is centered on tracing and analyzing women’s contributions to architectural institutions in Baghdad—both religious and civil—throughout the period under investigation. The study adopts the historical inductive and descriptive methodologies. It is structured into an introduction, two main sections, and a conclusion. The first section discusses the role of women in religious architectural institutions in Baghdad during the Early Abbasid period, while the second addresses their role in civil architectural institutions during the same period.The study reaches several significant findings, most notably:-  The prominent role of women in Baghdad during the Early Abbasid period in both religious and civil architectural institutions, whether among women of the Abbasid court, affluent women, or women from the general population. Their contributions included participation in the construction of palaces, mosques, schools, hospitals, bridges, and markets.-  Women’s role in supporting urban life in Baghdad during the Early Abbasid period through direct financial support and patronage of charitable projects, as well as through waqf (endowment) foundations that contributed to the sustainability of urban development and the service of the community.-  The role of certain women of the Abbasid court in promoting architectural and decorative arts, reflecting the extent of women’s influence on the flourishing of Baghdad’s urban environment during the period under study.
Keywords: Women; Religious and Civil Urban Architectural Institutions; Baghdad; Early Abbasid Period